Existence and Practice of Indigenous Mathematics in Karnali Province - Roka, Jasbir; Khatri, Tilak Bahadur (Academic Journal of Mathematics Education, 2021)
This article is helpful to find the existing indigenous mathematics in Karnali Province and its practices at the secondary level school. Karnali province has its own indigenous culture and knowledge system. In Karnali province, Deuda, Mayur dance, Paiseri dance, Khando dance are the main dances and songs that can give the concept of mathematics. Many mathematicians have given contribution to the development of mathematics based on indigenous culture and practice. The researchers have selected ten secondary mathematics teachers purposively. Thus, focus group discussion was conducted to collect information of this study. It is concluded that existing indigenous mathematical knowledge and different occupations related to mathematical information should be used in teaching learning process at school level mathematics classroom. It is also found that there are different mathematical beliefs and practices in the different regions of Karnali province. This study is beneficial to the policymakers, curriculum designers, mathematics teachers and students, further researchers and learners as well. It is also beneficial for the teachers who want to make their teaching-learning activities alive in the classroom. Further, this article has social and cultural value in the real life situation of the learners. It helps to the teachers to teach Mathematics from the social and cultural perspectives in the classroom at any level.